PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI DI UPT PENGELOLAAN KAWASAN CAGAR BUDAYA DINAS KEBUDAYAAN (KUNDHA KABUDAYAN) KOTA YOGYAKARTA (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
Good employee performance in the era of the industrial revolution as it is now is needed so that agencies can survive and compete with competitors. However, some employees are still experiencing a decline in performance which is partly due to frequent delays in completing tasks, obstacles in achieving work targets, work standards that do not meet expectations, and problem solving in the workplace that has not been optimal. To determine the effect of leadership style and work motivation on performance with job satisfaction as a mediating variable. Researchers used a population of employees in the UPT Management of Cultural Heritage Areas, Yogyakarta Cultural Office. The sampling technique used by researchers in this study was purposive sampling with a total sample of 80 employees. The data in this study is quantitative data, namely data in the form of numbers obtained from direct measurements from questionnaires distributed with google form. Data analysis in this study used The Structural Equation Model (SEM) with PLS analysis tools. Leadership style has a significant effect on job satisfaction. Work motivation has a significant effect on job satisfaction. Leadership style has no effect on employee performance. Work motivation has a significant effect on employee performance. Job satisfaction has a significant effect on employee performance. Job satisfaction acts as a mediator of the influence of leadership style on employee performance. Job satisfaction acts as a mediator of work motivation on employee performance.
Keywords: Leadership Style; Work Motivation; Job Satisfaction; Performance.